Two Cd(ii)-based metal–organic frameworks for the highly effective detection of Fe3+ ions and levofloxacin in aqueous media. Issue 42 (7th October 2021) - Fu, Miao-Miao; Liu, Ce; Dong, Gui-Ying
Abstract : Two new Cd(ii )-MOFs are hydrothermally synthesized and can be applied as dual-response sensors to identify Fe 3+ and levofloxacin (LVX) with high selectivity, sensitivity and excellent reusability. Abstract : Levofloxacin (LVX), as a broad-spectrum antibiotic, is ubiquitous in water environments due to its wide application and good water solubility, posing a certain threat to the ecological environment. Therefore, it is necessary to design a fluorescent sensor with an effective detection ability. In this work, two new Cd(ii )-based metal–organic frameworks (MOFs) [Cd(L)0.5 (tdc)·H2 O] n (1 ) and [Cd(L)0.5 (btec)0.5 ] n (2 ) (L = 1, 4-di(1 H -benzo[ d ]imidazol-2-yl)butane, H2 tdc = 2, 5-thiophenedicarboxylic acid, H4 btec = 1, 2, 4, 5-benzenetetracarboxylic acid) were hydrothermally synthesized and characterized. 1 presents a 2D hierarchical layer with a 3, 4L83 network, whereas 2 exhibits a 3D framework with fsh topology. The two Cd(ii )-MOFs exhibit superior thermal and chemical stability (pH = 3–12). 1 and 2 can selectively identify LVX with ultra-high sensitivity (0.01 μM and 0.02 μM), rapid response (in 30 s) and excellent selectivity in water. Meanwhile, 1 and 2 also can be efficient probes for detection of Fe 3+ ions with detection limits of 1.08 μM and 1.74 μM, respectively. Moreover, the two dual-response luminescent sensors exhibit remarkable reusability. The quenching mechanisms were also investigated from the perspective of energy transfer and photoinduced electron transfer (PET) in detail.